FROM CORPORATIONISM TO COOPERATIONISM: REVERSED GLOBALIZATION, COOPERATIVE POLITICS AND EXPANDING ONLINE COMMUNICATION IN POST-PANDEMIC TIME - FIEDLER, RADOSŁAW (Society Register, 2020)
In post-pandemic time a redefinition of politics and globalization is more than possible. There are a lot of possible scenarios – one of them is the cooperative model as an antidote to the polarized politics and corporative driven globalization. The aim of this short discussion paper is to present the proposal of the shift from corporationisim to cooperationism as a functional model in addressing challenges locally and globally.